Pandemic Crisis and Its Challenges to Security Studies - Jović, Dejan (Sociološki pregled, 2020)
The pandemic crisis in 2020 has given the cause for the securitization of the medical problem that might – if it goes on without an adequate answer – question security in many other sectors: economic, state, social and identity ones. It might have – and it already has – consequences for the structure of the international order as well. In this article the author identifies the consequences of the pandemic crisis at all four levels of the security analysis: individual, intrastate, interstate and global levels. Then it tests the main theses of the approaches and theories within security studies (realistic, liberal, constructivist and globalist), showing the manner in which the pandemic crisis has confirmed such theses and where it denied them. The article also reviews formerly unpublished analyses of this phenomenon and comments on them in a critical manner. The author concludes that the pandemic crisis has not completely ruined the reputation of any of those theories, not even the liberal-globalist one. However, the crisis has posed all of us some serious questions that need to be answered.